Normalization of puberty and adult height in girls with Turner syndrome: results of the Swedish Growth Hormone trials initiating transition into adulthood - Kriström, Berit; Ankarberg-Lindgren, Carina; Barrenäs, Marie-Louise; Nilsson, Karl Olof; Albertsson-Wikland, Kerstin (Frontiers in Endocrinology, 2023)
Objective To study the impact of GH dose and age at GH start in girls with Turner syndrome (TS), aiming for normal height and age at pubertal onset (PO) and at adult height (AH). However, age at diagnosis will limit treatment possibilities. Methods National multicenter investigator-initiated studies (TNR 87-052-01 and TNR 88-072) in girls with TS, age 3–16 years at GH start during year 1987–1998, with AH in 2003–2011. Of the 144 prepubertal girls with TS, 132 girls were followed to AH (intention to treat), while 43 girls reduced dose or stopped treatment prematurely, making n=89 for Per Protocol population. Age at GH start was 3–9 years (young; n=79) or 9–16 years (old; n=53). Treatment given were recombinant human (rh)GH (Genotropin® Kabi Peptide Hormones, Sweden) 33 or 67 µg/kg/day, oral ethinyl-estradiol (2/3) or transdermal 17β-estradiol (1/3), and, after age 11 years, mostly oxandrolone. Gain in heightSDS, AHSDS, and age at PO and at AH were evaluated. Results At GH start, heightSDS was −2.8 (versus non-TS girls) for all subgroups and mean age for young was 5.7 years and that of old was 11.6 years. There was a clear dose–response in both young and old TS girls; the mean difference was (95%CI) 0.66 (−0.91 to −0.26) and 0.57 (−1.0 to −0.13), respectively. The prepubertal gainSDS (1.3–2.1) was partly lost during puberty (−0.4 to −2.1). Age/heightSDS at PO ranged from 13 years/−0.42 for GH67young to 15.2 years/−1.47 for GH33old. At AH, GH67old group became tallest (17.2 years; 159.9 cm; −1.27 SDS; total gainSDS, 1.55) compared to GH67young group being least delayed (16.1 years; 157.1 cm; −1.73 SDS; total, 1.08). The shortest was the GH33young group (17.3 years; 153.7 cm: −2.28 SDS; total gainSDS, 0.53), and the most delayed was the GH33old group, (18.5 years; 156.5 cm; −1.82 SDS; total gainSDS, 0.98). Conclusion For both young and old TS girls, there was a GH-dose growth response, and for the young, there was less delayed age at PO and at AH. All four groups reached an AH within normal range, despite partly losing the prepubertal gain during puberty. Depending on age at diagnosis, low age at start with higher GH dose resulted in greater prepubertal height gain, permitting estrogen to start earlier at normal age and attaining normal AH at normal age, favoring physiological treatment and possibly also bone health, hearing, uterine growth and fertility, psychosocial wellbeing during adolescence, and the transition to adulthood.